An Update on the Prevalence and Characterization of H-PF4 Antibodies in Asian-Indian Patients - (:unkn) unknown (THIEME MEDICAL PUBL INC, 2009)
Heparin is the second most widely used anticoagulant/antithrombotic agent besides warfarin and is commonly used for various purposes such as treatment and surgical indications. A significant adverse effect of heparin treatment can occur when heparin binds platelet factor 4 (H-PF4) to form a complex that results in formation of H-PF4 antibodies, which in turn leads to platelet/endothelial cell activation followed by heparin-induced thrombocytopenia (HIT). Based on the heparin-induced platelet aggregation and enzyme-linked immunosorbent assay tests, the H-PF4 antibody (HIT antibody) was diagnosed in 6% of Indian patients undergoing cardiovascular surgery who received unfractionated heparin, but the frequency of occurrence rose to 15% when the patients were tested with the C-14-serotonin release assay. This highlights some methodological variations in the diagnosis of HIT antibodies. It was also found that all the HIT-positive patients were either homozygous or heterozygous for the Fc gamma RIIa polymorphism, which also highlights the role of this polymorphism in the occurrence of HIT. Very recent studies show that increases in HIT antibody production may also be due to heparin contaminants. Although these antibodies do not result in thrombocytopenia, contaminants in heparin may be capable of triggering a differential immunogenic response in comparison with contaminant-free heparin. Here we discuss the methodological differences in diagnosing HIT, the potential impact of contaminants in heparin, as well as future considerations.
Keywords: Heparin-PF4 antibody; diagnosis; Indian; heparin contaminant; HEPARIN-INDUCED THROMBOCYTOPENIA; ADVERSE CLINICAL EVENTS; LABORATORY DIAGNOSIS; RISK-FACTORS; INHIBITORS; THERAPY